Pinna nobilis, the Vanishing Giant: A Comprehensive Review on the Decline of a Mediterranean Icon - Ilenia Azzena; Chiara Locci; Noemi Pascale; Ilaria Deplano; Riccardo Senigaglia; Fabio Scarpa; Marco Casu; Daria Sanna (Animals, 2025)
This review addresses the critical conservation challenges faced by Pinna nobilis, the noble pen shell, a keystone umbrella species in Mediterranean marine ecosystems. Since 2016, the species has experienced catastrophic population declines due to mass mortality events likely driven by protozoan, bacterial, and viral infections. Despite these severe circumstances, small resilient populations persist in select estuaries and coastal lagoons across the Mediterranean, offering potential for recovery. We provide a comprehensive overview on research dedicated to Pinna nobilis’ biology, genetic variation, disease dynamics, and environmental factors influencing its survival, with a focus on refugia where populations still endure. Remarkably, recent studies have revealed signs of resistance in certain individuals and the potential for hybridisation with Pinna rudis. In this context, the possible impact of the increasing occurrence of hybridisation between Pinna nobilis and Pinna rudis on the conservation of their genetic diversity should be carefully considered. This review highlights the importance of ongoing conservation efforts including habitat restoration, protection of remaining populations, assessment of past and present genetic variability, and the development of captive breeding programmes. We aim to elucidate the need for continued studies on Pinna nobilis’ biodiversity, particularly its evolutionary dynamics, genetic makeup, and the interplay of environmental variables influencing its survival and persistence.